Internal inguinal ring closure by laparoscopy using homologous pericardium grafts in horses - Spagnolo,Julio David (2016)
ABSTRACT: The occlusion of inguinal ring is the treatment to avoid the inguinal hernia in horses. The aim of this study is evaluate the efficacy of homologous pericardium grafts for internal inguinal ring closure in horses, comparing mechanical or manual laparoscopic suture. Cross over study, using six healthy intact male Mangalarga breed horses aged between 3 and 12 years. Horses were operated under general anesthesia in 25º Trendelenburg position. Five laparoscopic portals were employed. Pericardium grafts measuring 4x5cm were anchored covering the left and right internal inguinal rings using either manual intracorporeal suture or laparoscopic stapler. Horses were followed-up during 11 weeks when were submitted to a laparoscopic control. Surgical time, trans and postoperative complications and effectiveness of internal inguinal closure were evaluated and statistically analyzed. The level of significance was set at 5% P<0.05. The procedures were realized without complications and the mean time required for manual and mechanical suture procedures differed significantly (67.8±15.3 and 14.1±2.1 min respectively; P<0.05). All manually sutured grafts remained in place and partial suture dehiscence with incomplete occlusion of the internal inguinal ring was observed in two stapled grafts. Non-severe complications were observed trans or postoperatively. One synechiae and three omental adhesions were observed by laparoscopic control on day 77, but without clinical relevance in the evaluated period. The use of homologous pericardium grafts was effectiveness to internal inguinal ring closure by laparoscopy. Mechanical suture was faster to perform than manual, but provided less satisfactory results concerning safety of graft fixation.